Perinatal lethal Gaucher disease due to compound heterozygosity of the splicing mutations in GBA gene - Tsai-Jung Lu; Tzu-Hung Hsiao; Jiaan-Der Wang; Feng-Chu Lo; Pei-Pei Jhan; Wei-Chih Chen (Elsevier, 2023)
Objective: In order to figure out the cause for two consecutive fetuses with nonimmune hydrops fetalis (NIHF) in a Taiwanese couple, whole-Exome Sequencing and Sanger Sequencing were applied for the family. Case report: The two fetuses developed NIHF at gestation age of 19 and 21 weeks, respectively. The clinical features included ascites and pleural effusion, flattened nasofrontal angle, skin edema, clenched hands, ambiguous genitalia, hepatosplenomegaly and fetal thrombocytopenia. Magnetic resonance imaging of the brain showed cerebellar hypoplasia and delayed cortical maturation. The GBA deleterious variants c.1505+5G > C and c.308-1G > A were both detected in the two fetuses. Conclusion: The report provided the precious experience of the clinical presentation of perinatal lethal Gaucher disease (PLGD) and advice on reproductive medicine for the next pregnancy in a couple. The novel genetic mutations identified in the study also contribute to the known spectrum of PLGD-related mutations.